The estimation of GFR and the adjustment for BSA in overweight and obesity: a dreadful combination of two errors - López-Martínez, Marina; Luis-Lima, Sergio; Morales, Enrique; Navarro-Díaz, Maruja; Negrín-Mena, Natalia; Folgueras, Tomás; Escamilla, Beatriz; Estupiñán, Sara; Delgado-Mallén, Patricia; Marrero-Miranda, Domingo; González-Rinne, Ana; Miquel-Rodríguez, Rosa María; et al. (International Journal of Obesity, 2020)
Background Obesity is an established risk factor for renal disease and for disease progression. Therefore, an accurate determination of renal function is necessary in this population. Renal function is currently evaluated by estimated glomerular filtration rate (GFR) by formulas, a procedure with a proven high variability. Moreover, the adjustment of GFR by body surface area (BSA) confounds the evaluation of renal function. However, the error of using estimated GFR adjusted by BSA has not been properly evaluated in overweight and obese subjects. Methods We evaluated the error of 56 creatinine- and/or cystatin-C-based equations and the adjustment of GFR by BSA in 944 subjects with overweight or obesity with or without chronic kidney disease (CKD). The error between estimated (eGFR) and measured GFR (mGFR) was evaluated with statistics of agreement: the total deviation index (TDI), the concordance correlation coefficient (CCC) and the coverage probability (cp). Results The error of eGFR by any equation was common and wide: TDI averaged 55%, meaning that 90% of estimations ranged from −55 to 55% of mGFR. CCC and cp averaged 0.8 and 26, respectively. This error was comparable between creatinine and cystatin-C-based formulas both in obese or overweight subjects. The error of eGFR was larger in formulas that included weight or height. The adjustment of mGFR or eGFR led to a relevant underestimation of renal function, reaching at least 10 mL/min in 25% of the cases. Conclusions In overweight and obese patients, formulas failed in reflecting real renal function. In addition, the adjustment for BSA led to a relevant underestimation of GFR. Both errors may have important clinical consequences. Thus, whenever possible, the use of a gold standard method to measure renal function is recommended. Moreover, the sense of indexing for BSA should be re-considered and probably abandoned.